Vstop v Evropsko Unijo v dolini Idrije - Ravnik, Mojca (Traditiones (Ljubljana), 2006)
Analyzed are the events that had taken place in the Idrija River Yally when Slovenia joind the European Union on May, 1, 2004. The villages on both sides of the river were the ones most affected by the newly established border between Italy and Yugoslavia after the Second World War. The months folloeing the entrance of Slovenia in the European Union were marked by nimber of festivites, cultural events, and encounters organized by the local population. These reflect the common traditional cultural elements that, rather than a nostalgic reconstruction, express a sincere relief after the traumas of the past.
Keywords: ethnology; etnologija; ljudsko življenje; ljudski običaji; ljudski prazniki; European Union; Evropska unija; Idrija; Kambreško; Beneška Slovenija; Slavia Friulana; Italija; Italy